Identification of Rigosertib for the Treatment of Recessive Dystrophic Epidermolysis Bullosa-Associated Squamous Cell Carcinoma - Velina S. Atanasova; Celine Pourreyron; Mehdi Farshchian; Michael Lawler; Christian A. Brown; Stephen A. Watt; Sheila Wright; Michael Warkala; Christina Guttmann-Gruber; Josefina Piñón Hofbauer; FUENTES BUSTOS, MARIA IGNACIA; Marco Prisco; et al. (My University, 2019)
Abstract Purpose: Squamous cell carcinoma (SCC) of the skin is the leading cause of death in patients with the severe generalized form of the genetic disease recessive dystrophic epidermolysis bullosa (RDEB). Although emerging data are identifying why patients suffer this fatal complication, therapies for treatment of RDEB SCC are in urgent need. Experimental Design: We previously identified polo-like kinase 1 (PLK1) as a therapeutic target in skin SCC, including RDEB SCC. Here, we undertake a screen of 6 compounds originally designated as PLK1 inhibitors, and detail the efficacy of the lead compound, the multipathway allosteric inhibitor ON-01910, for targeting RDEB SCC in vitro and in vivo. Results: ON-01910 (or rigosertib) exhibited significant specificity for RDEB SCC: in culture rigosertib induced apoptosis in 10 of 10 RDEB SCC keratinocyte populations while only slowing the growth of normal primary skin cells at doses 2 orders of magnitude higher. Furthermore, rigosertib significantly inhibited the growth of two RDEB SCC in murine xenograft studies with no apparent toxicity. Mechanistically, rigosertib has been shown to inhibit multiple signaling pathways. Comparison of PLK1 siRNA with MEK inhibition, AKT inhibition, and the microtubule-disrupting agent vinblastine in RDEB SCC shows that only PLK1 reduction exhibits a similar sensitivity profile to rigosertib. Conclusions: These data support a "first in RDEB" phase II clinical trial of rigosertib to assess tumor targeting in patients with late stage, metastatic, and/or unresectable SCC.
Keywords: pathway inhibitor rigosertib; management; risk; plk1; antineoplastic agents; apoptosis; carcinoma, squamous cell; cell cycle proteins; epidermolysis bullosa dystrophica; gene knockdown techniques; genes, recessive; glycine; humans; keratinocytes; molecular targeted therapy; protein-serine-threonine kinases; proto-oncogene proteins; rna, messenger; rna, small interfering; skin neoplasms; sulfones; mitogen activated protein kinase kinase; polo like kinase 1; protein kinase b; rigosertib; small interfering rna; vinblastine; antineoplastic agent; cell cycle protein; glycine; messenger rna; oncoprotein; polo-like kinase 1; protein serine threonine kinase; rigosertib; sulfone; adult; animal experiment; animal model; apoptosis; article; cancer inhibition; controlled study; disease association; drug efficacy; drug research; enzyme inhibition; epidermolysis bullosa dystrophica; female; follow up; human; human cell; in vitro study; in vivo study; keratinocyte; microtubule; mouse; nonhuman; priority journal; signal transduction; skin cell; squamous cell skin carcinoma; tumor xenograft; complication; drug effect; epidermolysis bullosa dystrophica; gene knockdown; genetics; metabolism; molecularly targeted therapy; recessive gene; skin tumor; squamous cell carcinoma